EMRE Is an Essential Component of the Mitochondrial Calcium Uniporter Complex - Sancak, Yasemin; Markhard, Andrew L.; Kitami, Toshimori; Kovács-Bogdán, Erika; Kamer, Kimberli J.; Udeshi, Namrata D.; Carr, Steven A.; Chaudhuri, Dipayan; Clapham, David E.; Li, Andrew A.; Calvo, Sarah E.; Goldberger, Olga; et al. (Science (American Association for the Advancement of Science), 2013)
The mitochondrial uniporter is a highly selective calcium channel in the organelle's inner membrane. Its molecular components include the EF-hand-containing calcium-binding proteins mitochondrial calcium uptake 1 (MICU1) and MICU2 and the pore-forming subunit mitochondrial calcium uniporter (MCU). We sought to achieve a full molecular characterization of the uniporter holocomplex (uniplex). Quantitative mass spectrometry of affinity-purified uniplex recovered MICU1 and MICU2, MCU and its paralog MCUb, and essential MCU regulator (EMRE), a previously uncharacterized protein. EMRE is a 10-ki loda Ito n, m etazoa ç-specific protein with a single transmembrane domain. In its absence, uniporter channel activity was lost despite intact MCU expression and oligomerization. EMRE was required for the interaction of MCU with MICU1 and MICU2. Hence, EMRE is essential for in vivo uniporter current and additionally bridges the calcium-sensing role of MICU1 and MICU2 with the calcium-conducting role of MCU.